Strategi Social Media Marketing Ashiaaap melalui Instagram - Fikri Muzakki Gumilar; Udung Noor Rosyad (Bandung Conference Series: Communication Management, 2022)
Abstract. The emergence of social media is a huge opportunity for business people especially those who do not have enough capital to distribute product information to all corners of the world. Small businesses can advertise their products across unlimited territories (even outside the country) and earn more without the need to rent a place in the middle of the city and incur excessive advertising costs with social media technology, one of which Ashiaaap products. In the era before web 2.0 (before 2000, there was also classifying it as web 1.0), only those who had knowledge of the web (programming or design) or capital owners were able to recruit programmers who were able to provide content (text, images, music) in the web. so the exchange of data that occurs is one-to-many or little-to-many. The features and opportunities available on social media are used as opportunities for business people to sell their products across regions with low cost (high cost) but high impact (big effect), and bring substantial income only with the capital of Instagram social media. Abstrak. Munculnya media sosial menjadi sebuah peluang yang sangat besar untuk para pelaku usaha terlebih mereka yang belum memiliki modal cukup besar dalam mendistribusikan informasi produk ke segala penjuru dunia. Pelaku usaha kecil bisa mengiklankan produknya lintas wilayah tanpa batas (bahkan hingga luar negara) dan mendapatkan penghasilan lebih tanpa perlu menyewa tempat di tengah kota dan mengeluarkan biaya iklan yang terlalu besar dengan teknologi media sosial, salah satunya produk Ashiaaap. Di era sebelum web 2.0 (sebelum tahun 2000, ada juga mengklasifikasikannya sebagai web 1.0), hanya mereka yang memiliki pengetahuan mengenai web (programming atau design) atau para pemilik modal yang mampu merekrut programmer yang mampu menyediakan konten (teks, gambar, musik) di web. sehingga pertukaran data yang terjadi adalah one-to-many atau sedikit-ke- banyak. Fitur dan kesempatan yang ada di media sosial ini dijadikan peluang oleh para pelaku usaha untuk menjual produknya lintas daerah dengan low cost (biaya rendah) tetapi high impact (efek besar), dan mendatangkan penghasilan yang cukup besar hanya dengan bermodal media sosial instagram.